2022
DOI: 10.4103/jfmpc.jfmpc_991_21
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of Internet addiction among the students of professional colleges in the Jammu region

Abstract: Background: With ever-increasing digitization, the internet has intertwined into the daily lives of users to a large extent. It holds tremendous educational benefits to college students; however, its excessive usage can lead to addiction and even psychological morbidities. Objectives: To determine the prevalence of internet addiction and its association with various factors including depression, anxiety, and stress. Materials and Methods: A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
5
11
0
Order By: Relevance
“…The present study did not find a difference in the IA prevalence considering the participants’ faculty subject area, which is in concordance with an earlier study among Croatian university students [ 35 ] and a recent study among Indian students [ 33 ], although a recent study from Egypt found that students who studied in the field of biomedicine a more prone to IA development [ 47 ] and study among Indian students published in 2020 showed that students who studied in the field of technical sciences are the most vulnerable for the development of IA [ 48 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study did not find a difference in the IA prevalence considering the participants’ faculty subject area, which is in concordance with an earlier study among Croatian university students [ 35 ] and a recent study among Indian students [ 33 ], although a recent study from Egypt found that students who studied in the field of biomedicine a more prone to IA development [ 47 ] and study among Indian students published in 2020 showed that students who studied in the field of technical sciences are the most vulnerable for the development of IA [ 48 ].…”
Section: Discussionsupporting
confidence: 93%
“…Considering the sex difference in IA, this study showed that IA was statistically more frequent among males than among females, which is consistent with several studies from different countries [ 17 , 28 , 31 , 32 , 33 ] as well as with the results of previous studies in Croatia [ 34 , 35 ] although some studies found that the IA is more frequent among females [ 26 , 36 ] and others did not discover the difference in IA considering sex [ 6 , 12 , 29 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our results underline the male prevalence of Internet addiction, in line with other studies carried out during the same period ( 97 , 98 ). Regarding gender differences, the literature indicates that men are generally attracted to sex sites and online games.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, our study also noted that males get addicted to the internet more than females and this is in keeping with the findings of Adiele and Olatokun in southwest Nigeria, 49 Kumari et al in Jammu, India 50 and Prakash et al in an Indian online cross-sectional study. 32 Also, the finding that spending more time on the internet, and risky behaviours such as smoking, use of drugs and alcohol use are associated with internet addiction was in tandem with the findings of Zenebe et al, 51 and Kupus et a.l 47 during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 92%